2016
DOI: 10.1111/eos.12262
|View full text |Cite
|
Sign up to set email alerts
|

Bonding performance and interfacial characteristics of short fiber‐reinforced resin composite in comparison with other composite restoratives

Abstract: The purpose of this study was to investigate the shear bond strength (SBS) and surface free-energy (SFE) of short fiber-reinforced resin composite (SFRC), using different adhesive systems, in comparison with other composite restoratives. The resin composites used were everX Posterior (EP), Clearfil AP-X (CA), and Filtek Supreme Ultra Universal Restorative (FS). The adhesive systems used were Scotchbond Multi-Purpose (SM), Clearfil SE Bond (CS), and G-Premio Bond (GB). Resin composite was bonded to dentin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
7
21
0
Order By: Relevance
“…It has been reported that the surface characteristics of resin composite forming the interface with the adhesive are not influenced by the type of resin composite because the fillers, both particulate glass fillers and fibers, are coated in silane to improve bonding with the resin matrix . Therefore, the initial bond strength of dental adhesives with resin composite was not influenced by type of resin composite . The results of the SBS test in this study were consistent with the previous study .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has been reported that the surface characteristics of resin composite forming the interface with the adhesive are not influenced by the type of resin composite because the fillers, both particulate glass fillers and fibers, are coated in silane to improve bonding with the resin matrix . Therefore, the initial bond strength of dental adhesives with resin composite was not influenced by type of resin composite . The results of the SBS test in this study were consistent with the previous study .…”
Section: Discussionsupporting
confidence: 89%
“…The present study found that the SBS values of universal adhesives with short fiber‐reinforced resin composite did not show any significant differences compared with those with other composite restoratives, regardless of the etching mode. It has been reported that the surface characteristics of resin composite forming the interface with the adhesive are not influenced by the type of resin composite because the fillers, both particulate glass fillers and fibers, are coated in silane to improve bonding with the resin matrix . Therefore, the initial bond strength of dental adhesives with resin composite was not influenced by type of resin composite .…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recent study indicated a higher bond strength of SFRC to dentin by using etch-and-rinse and two-step self-etch adhesives than one-step self-etch. 35 The lower marginal microleakage of SFRC Class II restoration compared to conventional composite (Z250) was reported by Garoushi et al; two types of composite resins were bonded using an etch-and-rinse adhesive. 26 The low bonding efficiency of one-step self-etch (G-aenial Bond) used along with SFRC in a study by Atalay et al was reported as a possible explanation for no significant difference between SFRC and other restorations in terms of fracture resistance.…”
Section: Discussionmentioning
confidence: 88%
“…A two‐step etch‐and‐rinse adhesive was used for two types of composite resins used in this study. The results of a recent study indicated a higher bond strength of SFRC to dentin by using etch‐and‐rinse and two‐step self‐etch adhesives than one‐step self‐etch . The lower marginal microleakage of SFRC Class II restoration compared to conventional composite (Z250) was reported by Garoushi et al; two types of composite resins were bonded using an etch‐and‐rinse adhesive .…”
Section: Discussionmentioning
confidence: 91%
“…With a major contribution, wetting properties of adhesives are affected by their surface free energy, this surface free energy is the result of dispersion force, polarity force, and hydrogen bonding; differences in bonding performance of commercial adhesives can be related to different surface free energy values, a material with a lower surface free energy will spontaneously wet out a surface with a higher surface free energy 24,25) . Therefore, the aim of this study was to evaluate the effect of adding spherically shaped, silver nanoparticles into one total-etch and two self-etch adhesive systems bonded to fluorotic enamel using micro-tensile bond strength (μTBS) test.…”
Section: Introductionmentioning
confidence: 99%